1990
DOI: 10.1128/iai.58.5.1421-1428.1990
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evidence for penetration of anti-O antibody through the capsule of Klebsiella pneumoniae

Abstract: The role of the capsule in the reaction with anti-O or anti-K serum was examined morphologically by the techniques of freeze-substitution and immunoelectron microscopy in two strains of Kkebsiella pneumoniae differing in virulence for mice. Strain Chedid (O1:K2), an encapsulated virulent strain, has a thicker capsule (150 nm) than the encapsulated avirulent strain 277 (O1:K2) (60 nm). Two morphologically recognizable domains in the capsule created by the arrangement of the capsular filaments were clearly seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
5
20
3
Order By: Relevance
“…2D). Since these data are consistent with those of LPS ladder patterns in SDS-PAGE and the structure is very similar to the LPSs of Pseudomonas aeruginosa (13) and Klebsiella pneumoniae (11), the layers detected in this study were probably the polysaccharide region of the LPS.…”
Section: Electron Microscopic Analysis Of Cell Surface Structures Of supporting
confidence: 88%
“…2D). Since these data are consistent with those of LPS ladder patterns in SDS-PAGE and the structure is very similar to the LPSs of Pseudomonas aeruginosa (13) and Klebsiella pneumoniae (11), the layers detected in this study were probably the polysaccharide region of the LPS.…”
Section: Electron Microscopic Analysis Of Cell Surface Structures Of supporting
confidence: 88%
“…The inner one-fourth of the layer consisted of fibers arranged rectangularly on the surface of the cell wall, and we thus assumed that the antibody may not reach this layer. The experiment using an immunogold labeling technique reported in a previous paper, which showed the gold label to be located on the capsular surface area, also supports this notion (9). Regarding the mechanism of capsule size increase after reaction with the antibody, the following two possibilities are considered.…”
Section: Effect Of Monovalent Igg On Capsulessupporting
confidence: 62%
“…An encapsulated strain 277 (01: K2) and nonencapsulated strain 8N3 (01) of K. pneumoniae were used throughout the experiments. The origin and the biological characteristics of these strains have already been described in previous papers (9,10…”
mentioning
confidence: 88%
“…A thin section of the whole cell showed that the surface layer is always associated with the underlying outer membrane with a space but not with direct contact. Since the thin section technique that we used is a mild fixation method that preserves the fragile bacterial surface structure well (12,18), the space between the outer membrane and the surface layer protein should not be an artifact. These observations thus suggest that the surface layer proteins are not integrated components of the outer membrane but part of the external layer intimately associated with the outer membrane.…”
Section: Image Processing Of the Regular Patternmentioning
confidence: 99%